Serum Concentrations of Transforming Growth Factor-Beta 1 in Predicting the Occurrence of Diabetic Retinopathy in Juvenile Patients with Type 1 Diabetes Mellitus - Katarzyna Zorena; Ewa Malinowska; Dorota Raczyńska; Małgorzata Myśliwiec; Krystyna Raczyńska (Journal of Diabetes Research)
In the present study, we have decided to evaluate if serum transforming growth factor-beta 1 (TGF-β1) concentrations may have diagnostic value in predicting the occurrence of diabetic retinopathy (DR) in juvenile patients with type 1 diabetes mellitus (T1DM). The study included 81 children and adolescents with T1DM and 19 control subjects. All study participants had biochemical parameters examined, underwent an eye examination, and 24-hour blood pressure monitoring. Moreover, serum concentrations of TGF-β1 were measured. The group of patients with T1DM and nonproliferative diabetic retinopathy (NPDR) had statistically significant higher serum levels of TGF-β1 (P=0.001) as compared to T1DM patients without retinopathy as well as the healthy control subject. The threshold serum TGF-β1 concentrations which had a discriminative ability to predict the presence of DR were calculated using the receiver operating characteristic (ROC) curves analysis and amounted to 443 pg/ml. The area under the ROC curve (AUCROC) was 0.80, and its population value was in the range of 0.66 to 0.94. The sensitivity and specificity were calculated to be 72% and 88%, respectively. Our results suggest that TGF-β1 serum concentrations may be an additional parameter in predicting the occurrence of DR in juvenile patients with T1DM.